Clinical characteristics of persistent frequent attenders in primary care: case–control study - Patel, Shireen; Kai, Joe; Atha, Christopher; Avery, Anthony; Guo, Boliang; James, Marilyn; Malins, Samuel; Sampson, Christopher James; Stubley, Michelle; Morriss, Richard K. (Oxford University Press, 2015)
Background. Most frequent attendance in primary care is temporary, but persistent frequent attendance is expensive and may be suitable for psychological intervention. To plan appropriate intervention and service delivery, there is a need for research involving standardized psychiatric interviews with assessment of physical health and health status.